Kajian Implementasi Bangunan Gedung Hijau di Indonesia berdasarkan Perspektif Pemangku Kepentingan - Dewi Nurhayati; Dewi Larasati; Hanson E. Kusuma (Universitas Sebelas Maret Surakarta, 2026)
A Study on Green Building Implementation in Indonesia from Stakeholder PerspectivesThe Implementing of Green Building (GB) in Indonesia faces multidimensional barriers due to differing stakeholder perceptions. This study compares the views of architects, civil servants, academics, and others on GB challenges and strategies. Using a sequential explanatory mixed-methods approach, survey data from 137 respondents were analyzed. Results reveal a regional GB policy knowledge gap, with roughly 40% of architects and the public lacking understanding. While high investment costs are the primary barrier, solutions are polarized: professionals advocate for regulations, whereas the public emphasizes education. These findings highlight the need for a dual-track strategy combining regulations, fiscal incentives, and public education. Supported by collective leadership, this integration fosters a sustainable construction ecosystem that is legislatively compliant and socially embraced.